Impact of Charlson Comorbidity Index adjusted to age in prognosis after endovascular abdominal aortic aneurysm repair - Oliveira,Vânia Constâncio (2022)
Abstract Background: Individualized risk assessment using comorbidity adjustment is an important component in modern clinical practice and can be performed considering individual comorbidities or through the use of summary measures. The Charlson Comorbidity Index adjusted to age (CCIa) is the most widely validated and used comorbidity assessment tool. Studies have proved CCIa as a strong predictor of mortality for a variety of medical and surgical conditions; however, its utility in patients submitted to elective endovascular abdominal aortic aneurysm repair (EVAR) has not been studied. Methods: Patients submitted to EVAR between January 1, 2017 and December 31, 2021 in our tertiary, academic Vascular Surgery Department were retrospectively evaluated and 123 patients fulfilled the inclusion criteria. Patient characteristics and peri-operative variables were collected and CCIa was calculated. Surgical complications were classified according to Clavien-Dindo. The area under the curve of the receiver operating characteristic curves was calculated to validate and determine the discriminating ability of CCIa in predicting complications and mortality and the Youden index used to determine the critical value. Results: Mean age was 73.49±7.95 years and mean follow-up was 30.55±16.49 months. 30-day complication rate was 16%, 30-day mortality 1.63% and overall mortality 16%. Patients with higher CCIa had higher overall mortality (p=.002) but CCIa had no impact on 30-day complication rate and on 30-day mortality. Logistic regression showed that even after adjusting for patient´s comorbidities individually, CCIa was the only independent mortality predictor (p=.003). The optimal cutoff associated with higher overall mortality was found to be ≥6. Conclusion: CCIa does not seem to predict complications and early mortality after EVAR but it seems to be a useful predictor of mid-term survival after EVAR. These results show the limited role of this score in predicting outcomes after surgery but may help identify a sub-population whose shorter life-expectancy should be considered towards the benefits of EVAR.